Credit, Asset Prices and Monetary Policy - Leif Brubakk; Gisle James Natvik (Norges Bank, 2010)
Based on the established literature, we develop a structural model for the Norwegian economy that incorporates feed-backs from asset prices and credit to the real economy. We then use this framework for policy analysis, focusing on the role of asset prices and credit under optimal simple monetary policy rules.
hdl:11250/2507740
Keywords: 330